Effect of Using Recycled Local Solid Waste Materials On Creep Properties of Asphalt Mixtures - Abed Ali, Abdul Haq H.; Abbas, Alaa Saadi (Nahrain University College of Engineering Journal, 2011)
Numerous waste materials result from manufacturing operations in industries. The purpose of this study was to investigate the effect of these waste materials on physical properties of asphalt cement and on surface layer of hot mix asphalt pavement. Asphalt cement with penetration grade (40-50) and 19 mm aggregate maximum size gradation is used in this study with Optimum asphalt content 4.9 %. at the desired temperature of (25 C).Two types of waste materials crushed glass and sawyer wood (both retained on sieve no. 200) with four percentages (0%, 3%, 6%, and 9% byweight of total aggregate) are used. The mixes aretested by using creep test. From the experimental work, it can be seen that more benefits when additive waste glass or sawyer wood luck improvedmechanical (physical) and rheological properties for asphalt paving mixture